1999
DOI: 10.1063/1.124918
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent self-oscillations in a spatially direct GaAs/AlGaAs superlattice

Abstract: Articles you may be interested inSpontaneous quasi-periodic current self-oscillations in a weakly coupled GaAs/(Al,Ga)As superlattice at room temperature Appl.We report the observation of self-sustained photocurrent oscillations in a weakly coupled spatially direct intrinsic GaAs/Al 0.3 Ga 0.7 As superlattice. The oscillations are attributed to the dynamics of unstable electric field domains related to the ⌫Ϫ⌫ e1-e2 tunneling resonance. The observed oscillation period is much longer than the carrier recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, when the frequency decreases with increasing bias within the plateau, the electricfield profile oscillates around an almost uniform stationary state [100], which is typical for a rather low doping density. The bias dependence of the frequency for photocurrent oscillation in undoped, photoexcited SLs was also investigated experimentally by Kwok et al [177], Hosoda et al [227], Mimura et al [228], Ohtani et al [229,230,[241][242][243] and Tomlinson et al [231]. Unfortunately, there is no unique trend observed.…”
Section: Voltage Biasmentioning
confidence: 94%
See 1 more Smart Citation
“…However, when the frequency decreases with increasing bias within the plateau, the electricfield profile oscillates around an almost uniform stationary state [100], which is typical for a rather low doping density. The bias dependence of the frequency for photocurrent oscillation in undoped, photoexcited SLs was also investigated experimentally by Kwok et al [177], Hosoda et al [227], Mimura et al [228], Ohtani et al [229,230,[241][242][243] and Tomlinson et al [231]. Unfortunately, there is no unique trend observed.…”
Section: Voltage Biasmentioning
confidence: 94%
“…However, the undamped nature of the photocurrent oscillations in these two systems may be connected with the rather long lifetime of electrons in the X state of the AlAs barrier, which at least for the HFD occurs in both samples. Tomlinson et al [231] detected undamped photocurrent oscillations in an undoped GaAs/Al 0.3 Ga 0.7 As SL, where the transport in the LFD as well as HFD is governed by resonant tunnelling between states. Theoretical and experimental investigations of multiple-quantum-well structures have shown that under optical excitation with infrared light, which excites carriers from the lowest conduction subband into continuum states, periodic EFDs are formed due to the excitation of recharging waves [232][233][234].…”
Section: Monopole and Dipole Oscillations In Weakly Coupled Slsmentioning
confidence: 99%
“…Thereby, the different regions separated by domain walls get unstable and hence cause the oscillations. The resonance frequency can be tuned by the bias voltage or laser power [63,64]. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Many works were devoted also to studies of domain properties (see, e.g., [2] and references therein). Most of them were performed with weakly doped SLs at low temperatures under strong illumination [2][3][4][5][6][7]. The change in free carrier concentration under illumination gives rise to different domain regimes.…”
mentioning
confidence: 99%